Career Development of Generation Z Employees: The Role of Organizational Support, Performance, and Job Fit - Insan, Muhammad Yalzamul; Batubara, Soulthan Saladin (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aims to analyze the effects of organizational support, fairness in performance appraisal systems, and person–job fit on the career development of Generation Z employees working in the micro, small, and medium enterprise (MSME) sector in Indonesia. Using a quantitative approach and path analysis, the study examines differences in perceptions based on employment status and tests a theoretical model incorporating self-efficacy and career adaptability as mediating variables. The findings indicate that both organizational and individual factors play a crucial role in shaping career attitudes and employees’ organizational attachment. These results provide strategic implications for human resource management, particularly in fostering a supportive and fair work environment to encourage proactive and sustainable career development.